Toxic effects of daily applications of 10% carbamide peroxide on odontoblast-like MDPC-23 cells - Lima, Adriano Fonseca; Ribeiro, Ana Paula Dias; Soares, Diana Gabriela Sousa [UNESP]; Sacono, Nancy Tomoko; Hebling, Josimeri; De Souza Costa, Carlos Alberto [UNESP] (MJS Publishing, Medical Journals Sweden AB, 2013)
Background. Tooth bleaching has been widely studied, mainly due to the possible undesirable effects that can be caused by this esthetic procedure. The cytotoxicity of the bleaching agents and its components to pulp cells has been demonstrated in several researches. The aim of this study was to evaluate the toxic effects of successive applications of 10% carbamide peroxide (CP) gel on odontoblast-like cells. Materials and methods. Enamel-dentin discs obtained from bovine incisors were adapted to artificial pulp chambers (APCs). The groups were formed as follows: G1: Without treatment (control group); G2: 10% carbamide peroxide, CP (five applications/one per day); G3: 10% CP (one unique application); and G4: 35% hydrogen peroxide, HP (three applications of 15 min each). After treatment, cell metabolism (MTT), alkaline phosphatase (ALP) activity and plasma membrane damage (flow cytometry) were analyzed. Results. Reductions in cell metabolism and alkaline phosphatase activity along with severe damage of the cytoplasmic membrane were noted in G2. In G3, no damage was observed, compared to the control group. Intermediary values of toxicity were obtained after 35% HP application. Conclusion. It can be concluded that one application of 10% CP did not cause toxic effects in odontoblast-like cells, but the successive application of this product promoted severe cytotoxic effects. The daily application of the bleaching agents, such as used in the at-home bleaching technique, can increase the damages caused by this treatment to the dental pulp cells. © 2013 Informa Healthcare.
Keywords: Carbamide peroxide; Hydrogen peroxide; Odontoblasts; Tooth bleaching; Toxicity